Contemplating the Afterlife of Slavery - Stephane Martin Demers (Caribbean Studies Students' Union, 2022)
Évelyne Trouillot's novel The Infamous Rosalie makes it abundantly clear that slavery was deeply ingrained in all aspects of an enslaved person's life. Enslaved expectant mothers in late-eighteenth-century Saint-Domingue contemplated the afterlife of slavery through acts of gynecological resis- tance such as abortion and infanticide as well as marronage both in the novel and as a historical actuality. These acts of resistance laid the groundwork for the development of a collective liberation mentality among slaves necessary for the emergence of an independent Haiti and the creation of the first Black Repub- lic. Black counter-historical narratives, such as Trouillot's novel, can provide historians with a vantage point from which to understand how historical actors who are often silenced were some of the greatest agents of change and justice in the modern era. Enslaved women should occupy a space in scholarly literature and historical discourse that honors their actions as active agents in search of collective liberation and independence.